2005
DOI: 10.1086/429410
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Sexual Transmission of Human T Lymphotropic Virus (HTLV)–I and HTLV‐II

Abstract: The incidence of sexual transmission of HTLV-II may be similar to that of HTLV-I, and female-to-male transmission may play a more important role than previously thought. HTLV-I and -II proviral load may be lower in sexually acquired infection, because of a small infectious dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 37 publications
3
75
0
12
Order By: Relevance
“…Sexual partnership with an IDU was significantly more frequent among the patients in the HCV/HTLV-2 group, thus suggesting that they were at greater risk of HTLV-2 acquisition through sexual means. However, even though HTLV-1 and HTLV-2 have been acknowledged to be sexually-transmitted agents 26 35 38 , recent evidence has suggested that transmission is not particularly associated with any of the HTLV types 30 . Alternatively, and speculatively, the increased risk of HTLV-2 acquisition among these individuals may have been due to non-reported IDU, as previously described in a serological survey of HCV coinfection among people living with HIV in Santos, Brazil 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Sexual partnership with an IDU was significantly more frequent among the patients in the HCV/HTLV-2 group, thus suggesting that they were at greater risk of HTLV-2 acquisition through sexual means. However, even though HTLV-1 and HTLV-2 have been acknowledged to be sexually-transmitted agents 26 35 38 , recent evidence has suggested that transmission is not particularly associated with any of the HTLV types 30 . Alternatively, and speculatively, the increased risk of HTLV-2 acquisition among these individuals may have been due to non-reported IDU, as previously described in a serological survey of HCV coinfection among people living with HIV in Santos, Brazil 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Roucoux et al 65 observed lower HTLV-1/2 proviral loads in patients with sexually acquired infections compared with HTLV-1/2-positive index patients who transmitted HTLV, most likely because of the small infectious dose that is required for the sexual transmission of the virus.…”
Section: Sexual Transmissionmentioning
confidence: 99%
“…In addition, the epidemiology of HTLV, particularly its tendency to occur in clusters, has enabled the identifi cation of groups who are at risk for exposure, including injection drug users 34,56,59 , sex workers 50,[55][56][57][58][59][60][61][62] , men who engage in intercourse with other men 52,53,56 , recipients of blood transfusions in Brazil before November 1993 63 , and sexual partners of known HTLV carriers [64][65][66] (Figure 2). …”
Section: Sexual Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of HTLV transmission in non-IDU detected 2 HTLV-2 seroconvertors, 1 maleto-female, the other female-to-male. Of note, both seropositive partners of the seroconvertors reported a history of prior STI and rarely to never used condoms [26]. Another plausible explanation for increased rates of HTLV-2 in females is that younger females are more likely to have sexual relationships and/or share injection equipment with older male IDU, a group with higher rates of HTLV-2 infection.…”
Section: Discussionmentioning
confidence: 99%